Multi-Layered Distributed Control for Collective Movement and Coverage of Robot Swarms in Unknown Structured Environments - Pham Duy Hung; Trung Dung Ngo (IEEE Access)
In this study, we propose a novel multi-layered distributed control (MDC) framework for multi-robot deployment and coverage strategies in unknown structured environments. The MDC is structured with strategic function-based layers of swarm deployment, coverage, and withdrawal built on top of the underlying behavior-based motion control layer. The behavior-based motion control layer is responsible for preserving the network integrity and guaranteeing collision avoidance for mobile robots. To enable adaptability and flexibility of control strategies in various unknown structured environments, the behavior suppression mechanism is created to modulate and substitute individual behaviors for appropriate swarm strategies including swarm movement in aggregation, one-chain configuration, collective coverage with target-tracking motions. We have examined and evaluated our proposed method through both simulation and real-world experiments. The results demonstrate that the MDC achieves high performance in both task completion and coverage rate while maintaining flexibility and scalability, highlighting its potential for real-world applications.